The clash of business models in emerging economies: The case of wind energy industry in Africa - Derek Campbell; Mike Danilovic; Fawzi Halila; Maya Hoveskog (The International Journal of Management Science and Information Technology (IJMSIT), 2013)
With the rise of emerging economy EE as main engine of global growth, the intensified competition in the wind energy industry and internationalization to EE, enterprises need to rethink and innovate their business models in order to succeed. The overall purpose of this article is to increase our understanding of the drivers of business model innovation (BMI) in EE, particularly in the wind energy industry. Qualitative, multi-case design is applied, where three cases within wind energy industry in Africa are studied - Siemens (Germany), Suzlon (India) and Goldwind (China). The results show that there is a difference between 'Developed-country Multinational Enterprises' (DMNEs), such as Siemens, and 'Emerging-county Multinational Enterprises', such as Suzlon and Goldwind, in the way they approach BMI in EE. To gain a competitive advantage in EE requires capabilities to deal with the specific EE related drivers of change: 1) fast growth and high demand combined with high uncertainty; 2) lower level of market-oriented socioeconomic development; 3) stronger governmental influence on the market; and 4) the need for simple, cheap and easy to maintain technologies. Therefore, it is important that managers position their enterprises in the EE first as local players and only then as multinationals. Our study indicates that future research should focus on the main elements and the drivers of change that would shape BMI by adding new variables, specifically related to EE.
Keywords: 650; business model innovation; emerging economies; EMNEs; DMNEs